pH-Dependent Water Clusters in Photoacid Solution: Real-Time Observation by ToF-SIMS at a Submicropore Confined Liquid-Vacuum Interface - Liu, Ying-Ya; Hua, Xin; Zhang, Zhiwei; Zhang, Junji; Zhang, Shaoze; Hu, Ping; Long, Yi-Tao (Frontiers in Chemistry, 2020)
Water clusters are ubiquitously formed in aqueous solutions by hydrogen bonding, which is quite sensitive to various environment factors such as temperature, pressure, electrolytes and pH. Investigation of how the environment has impact on water structure is important for further understanding of the nature of water and the interactions between water and solutes. In this work, pH-dependent water structure changes were studied by monitoring the changes for the size distribution of protonated water clusters by in-situ liquid ToF-SIMS. In combination with a light illumination system, in-situ liquid ToF-SIMS was used to real-time measure the changes of a light-activated organic photoacid under different light illumination conditions. Thus, the proton transfer and pH-mediated water cluster changes were analyzed in real-time. It was found that higher concentration of free protons could lead to a strengthened local hydrogen bonding network as well as relatively larger protonated water clusters in both organic acid and inorganic acid. Besides, the accumulation of protons at the liquid-vacuum interface under light illumination was observed owing to the affinity of organic molecules to the low-pressure gas phase. The application of in-situ liquid ToF-SIMS analysis in combination with in-situ light illumination system opened up an avenue to real-time investigate light-activated reactions. Besides, the results regarding water structure changes in acidic solutions showed important insights in related atmospheric and physiochemical processes.